Cell- and stage-specific localization of galectin-3, a β-galactoside-binding lectin, in a mouse model of experimental autoimmune encephalomyelitis. (September 2018) - Itabashi, Tetsuya; Arima, Yasunobu; Kamimura, Daisuke; Higuchi, Kotaro; Bando, Yoshio; Takahashi-Iwanaga, Hiromi; Murakami, Masaaki; Watanabe, Masahiko; Iwanaga, Toshihiko; Nio-Kobayashi, Junko
Abstract: Multiple sclerosis (MS) is an autoimmune disease in which pathogenic T cells play an important role, and an experimental autoimmune encephalomyelitis (EAE) is used as an animal model of MS. Galectins are β -galactoside-binding lectins and involved in various physiological and pathological events. Among fifteen members of galectins, galectin-1, -8, and -9 play immunosuppressive roles in MS and EAE; however, the role of galectin-3 (gal-3) is complex and controversial. We examined expression of gal-3 in the spinal cord and nerve roots of EAE mice. No immunohistochemical signals were detected in naïve mice, whereas gal-3 appeared at lower lumbar levels of the spinal cord and nerve roots in EAE mice. In the spinal cord, gal-3-positive cells were activated microglia and/or infiltrating macrophages, which were round in shape and intensified for the lysosomal enzyme, cathepsin D, indicating elevated phagocytic activity. Gal-3-positive cells in the spinal cord were most abundant during the peak symptomatic period. In the recovery period, they disappeared from the spinal parenchyma but remained at moderate levels in the pia mater. Interestingly, gal-3-positive cells selectively appeared in ventral, but not dorsal, nerve roots running through the spinal canal, with expression peaking during the recovery period. In ventral nerve roots, the major cell type expressing gal-3 was a specific population of Schwann cells that surround unmyelinated axons and express the biosynthetic enzyme forl -serine, a potent neurotrophic amino acid. Gal-3 was also induced in Iba1/F4/80-positive macrophages, which engulf damaged myelin and axon debris. Thus, gal-3 is induced in distinct cell types that are engaged in removal of damaged axons and cell debris and axon regeneration and remyelination, suggesting a potential neuroprotective role of gal-3 in EAE mice. Graphical abstract: Highlights: Gal-3 + cells appear in spinal parenchyma during EAE progression period. Gal-3 + microglia and macrophages contain abundant cathepsin D -positive lysosomes. Gal-3 + Schwann cells increase in number in ventral roots during recovery period.